2017
DOI: 10.1002/asna.201713389
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy overdensities around 3C radio galaxies and quasars at 1 < z < 2.5 revealed by Spitzer 3.6/4.5 µm and Pan‐STARRS

Abstract: Luminous radio sources are thought to lie in galaxy clusters or proto-clusters. The complete sample of 64 high-redshift 3C sources at 1 < z < 2.5 has been mapped with the Spitzer Space Telescope. The IRAC 3.6 and 4.5 μm 5 detection limit of 4 μJy (22.4 AB mag) allows us to search for the brightest candidate cluster member galaxies associated with the 3C sources. To remove the contamination of foreground stars and galaxies along the lines of sight toward the 3C sources, we apply color cuts: the removed sources … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…We calculate the COD (= SDC -SDP) by two approaches, one using for each 3C its individual periphery and one using the average of all peripheries. Finally we compare with previous findings by Kotyla et al (2016) and Ghaffari et al (2017).…”
Section: Significance and Frequency Of Overdensitiessupporting
confidence: 60%
See 3 more Smart Citations
“…We calculate the COD (= SDC -SDP) by two approaches, one using for each 3C its individual periphery and one using the average of all peripheries. Finally we compare with previous findings by Kotyla et al (2016) and Ghaffari et al (2017).…”
Section: Significance and Frequency Of Overdensitiessupporting
confidence: 60%
“…Based on Sloan Digital Sky Survey (SDSS) data of about 500 galaxies at z < 0.4, Strateva et al (2001) found that u − r = 2.22 separates passive and and star-forming galaxies, as expected from their different stellar populations. Secondly, we have cross matched the two-filter-detected HST sample with the Spitzer/IRAC 3C sample of Ghaffari et al (2017). For (the limited number of) unique matches, the supposed red sources at z > 1 with F140W −[3.6] > 1 show an average color F606W -F140W = 2.8 ± 0.8.…”
Section: Color-magnitude Diagramsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the host galaxy of 3C 298, there is currently insufficient molecular gas for the galaxy to grow in stellar mass to match the mass predicted by the local scaling relationship. Furthermore, the quasar 3C 298 does not appear to live in an overdense environment based on the number count of galaxies seen with the Spitzer Space Telescope imaging data (Ghaffari et al 2017). The open question is, how do these galaxies obtain the stellar mass necessary to grow into the massive galaxies we see today?…”
Section: Offset From Local Scaling Relationsmentioning
confidence: 99%